The Influence of Product Quality and Brand Image on Purchase Decisions of Nescafe Coffee in Packaging Ready to Drink in Surabaya City - Maulida Zulfania; Ugy Soebiantoro (Indonesian Journal of Business Analytics, 2023)
In the current era, people no longer spend a lot of time waiting for the manufacturing process, but prefer consume instant beverage products because they are save time but can still increase productivity. This study is anticipated to be able to examine how brand perception and product quality affect consumer buying behavior for Nescafe coffee in ready-to-drink packages. Purposive sampling is used in this quantitative data collection procedure using 104 responders as the sample size. Partial Least Square (PLS) was used in this study's data analysis method. According to the study's findings, it can be concluded that the product quality and the brand image have a significant positive effect on purchasing decisions.